B vitamins and diseases of the nervous system: A review - Pavel R. Kamchatnov; Alexandr V. Chugunov; Alexey A. Kabanov (ZAO "Consilium Medicum", 2023)
B vitamins (neurotropic vitamins) are involved in numerous reactions in the nervous tissue. Their deficiency is associated with a variety of neurological disorders. The article discusses the effectiveness and safety of the use of neurotropic vitamins in the most common diseases of the central and peripheral nervous system. The results of clinical studies of the drug Neuromultivit are analyzed.